Use of modeling techniques in learning skills make doormat against children with intellectual impairment - Ai Sri Wahyuni; Ratih Listyaningtyas; Sistriadini Alamsyah Sidik (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2020)
This research is motivated by the problems that researchers found in SKh Sutmaemun Serang-Banten, namely in children with intellectual disabilities in class VII. In learning the skills of making doormats. This study aims to determine whether there is a significant influence with the use of modelling techniques to improve the ability to make doormats in children with intellectual disabilities. This type of research is Single-Subject Research. Data collection techniques used are using tests to assess learning outcomes making doormats and observations are used data collection techniques by observing each behavior displayed by the subject. The subjects involved in this study were 1 child. The results obtained by the subjects were seen from the frequency indicated at baseline 1, with the intervention condition experiencing an increase of 88.8%, as well as the average acquisition for the baseline condition 2 66.6% increased compared to the baseline 1 condition which was 44.4% points. it means that modelling techniques can influence the learning of skills in making doormats.